Anatomical and physiological features of the basal seat area tissues in edentulous jaws. the doctrine of the dentures fixation in edentulous jaws. impression making in edentulous patients - Томилин, Вячеслав Геннадиевич; Tomilin, V. (My University, 2015)
1.To introduce the anatomical and physiological features of the basal seat area tissues in edentulous jaws. 2.To introduce the doctrine of the dentures fixation in edentulous jaws. 3.To introduce the impression making in edentulous patients.
Keywords: anatomical and physiological features; basal seat area tissues